Death of a Software Ecosystem: A Developer Relations (DevRel) Perspective - Massanori, Daniel; Cafeo, Bruno B. P.; Wiese, Igor; Fontão, Awdren (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
The Developer Relations (DevRel) is a strategy to attract, engage and mature developers in contributing to a platform. It supports the establishment of a Software Ecosystem (SECO). However, even with investments in the DevRel, some organizations face the death of their ecosystems, for example: Symbian (2012), Firefox OS (2016), Windows Phone (2017). It can also be compared based on Ecology to a disruption of the "food chain" that can turn a dynamic ecosystem in a static or dead ecosystem. For example, Microsoft announced in 2017 that Windows Phone would no longer push any updates and became only focusing on maintenance. We want to contribute in understanding how, why and when a SECO is turning on static (i.e., dying) and the "post mortem" status of a SECO. We initially study the Windows Phone from 46,030 questions in Stack Overflow to understand what happens to a SECO when the core platform is discontinued. From our result analysis we perceived that it can be useful to understanding the "vital signals" of ecosystem collapse, migratory/survival patterns, technical resource recycling and the energy transfer among individuals, populations, communities and SECOs. We also contributes with 14 insights.